Uskorenie vosstanovlenija posle travm verchnich konecnostej u kvalificirovannych bokserov s pomošc'ju kineziotejpirovanija - Gurova, A.; Vertebnaia, A. (Science in Olympic Sport, 2017)
It is shown that injuries of the upper extremities in boxer athletes may slow down the improvement of sports mastery. The use of the kinesio- taping method results in a more rapid recovery of injured muscles and joints and, therefore, accelerates the return to training and competition. The method of kinesio taping is more efficient when combined with other means of rehabilitation (massage, therapeutic gymnastics, physiotherapy) and is able to improve the biomechanics of movements. It was found that kinesio taping in the area of injured upper extremities in boxers results in increased range of motion in the joints and in reduced pain and swelling. The comparison of the goniometry data before and after the use of kinesiology tape showed a positive dynamics of the increase in the range of motion in all injured joints.